Impact of Time-to-Reperfusion on Outcome in Patients with Poor Collaterals - Hwang, Y.-H.; Kang, D.-H.; Kim, Y.-W.; Kim, Y.-S.; Park, S.-P.; Liebeskind, D.S. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: The relationship between reperfusion and clinical outcome is time-dependent, and the effect of reperfusion on outcome can vary on the basis of the extent of collateral flow. We aimed to identify the impact of time-to-reperfusion on outcome relative to baseline angiographic collateral grade in patients successfully treated with endovascular revascularization for acute large-vessel anterior circulation stroke. MATERIALS AND METHODS: Two hundred seven patients were selected for analysis from our prospectively maintained registry. Inclusion criteria were M1 MCA ± ICA occlusions, onset-to-puncture time within 8 hours, and successful endovascular reperfusion. Baseline angiographic collateral grades were independently evaluated and dichotomized into poor (0–1) versus good (2–4). Multivariable analyses were performed to identify the effect of collateral-flow adequacy on favorable outcome on the basis of onset-to-reperfusion time and puncture-to-reperfusion time. RESULTS: In the poor collateral group, the odds of favorable outcome significantly dropped for patients with onset-to-reperfusion time of >300 minutes or puncture-to-reperfusion time of >60 minutes (onset-to-puncture time: ≤300, 59% versus >300, 32%; OR, 0.24; P = .011; puncture-to-reperfusion time: ≤60, 73% versus >60, 32%; OR, 0.21, P = .011), whereas the probability of favorable outcome in the good collateral group was not significantly influenced by onset-to-reperfusion time or puncture-to-reperfusion time. In the subgroup lesion-volume growth analysis by using DWI, the effect of puncture-to-reperfusion time of >60 minutes was significantly greater compared with the effect of puncture-to-reperfusion time of <60 minutes in the poor collateral group (β = 41.6 cm3, P = .001). CONCLUSIONS: Time-to-reperfusion including onset-to-reperfusion time and puncture-to-reperfusion time in patients with poor collaterals is an important limiting factor for favorable outcome in a time-dependent fashion. Future trials may benefit from a noninvasive imaging technique to detect poor collaterals along with a strategy for rapid reperfusion. HIhemorrhagic infarctionOPTonset-to-puncture timeORTonset-to-reperfusion timePHparenchymal hematomaPRTpuncture-to-reperfusion time